2018
DOI: 10.1186/s40360-018-0212-7
|View full text |Cite
|
Sign up to set email alerts
|

Adefovir dipivoxil induced hypophosphatemic osteomalacia in chronic hepatitis B: a comparative study of Chinese and foreign case series

Abstract: BackgroundAdefovir dipivoxil (ADV)-induced renal tubular dysfunction and hypophosphatemic osteomalacia (HO) have been given great consideration in the past few years. However, no standard guidance is available due to a lack of powerful evidence from appropriate long-term prospective case-control studies and variations in the definition of renal adverse events. The aim of this study is to clarify clinical features of ADV-related HO in Chinese chronic hepatitis B patients with long-term ADV treatment in Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Our case was also a 55 year old male supporting the results of Chen et al (13). We observed right hip fracture and treated the patient conservatively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our case was also a 55 year old male supporting the results of Chen et al (13). We observed right hip fracture and treated the patient conservatively.…”
Section: Discussionsupporting
confidence: 90%
“…Our case was 55 year-old man receiving ADV therapy for 120 months. Chen et al (13) have studied ADV induced hypophosphatemic osteomalacia in Chinese and non Chinese patients and found out that middle aged men are affected more in both groups and its not associated with nationality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al reported that a misdiagnosis of ADV-induced Fanconi syndrome was observed in 27 out of 120 patients. The misdiagnoses included osteoporosis (18.0%), ankylosing spondylitis (16.0%), vertebral disc herniation (12.0%), osteoarthropathy (10.0%), and bone tumors (10.0%) (23).…”
Section: Discussionmentioning
confidence: 99%
“…44 Hypophosphatemia occurs after ADV treatment for 1 year in a time- and dose-dependent manner, and HO appears after 3 to 4 years of treatment. 35 eGFR is considered the best indicator of renal function in patients with chronic renal disease, 45 but some researchers consider eGFR and cystatin C (Cys-C) more sensitive indices of kidney function than serum creatinine in patients with ADV-induced FS. However, other studies describe eGFR as the best index.…”
Section: Reviewmentioning
confidence: 99%